Impact of mesospheric intrusions on ozone-tracer relations in the stratospheric polar vortex - Müller, R.; Tilmes, S.; Nakajima, H.; Grooß, J.-U.; Engel, A.; Oelhaf, H.; Wetzel, G.; Huret, N.; Pirre, M.; Catoire, V.; Toon, G. (Journal of Geophysical Research, 2007)
[1] Ozone-tracer relations are used to quantify chemical ozone loss in the polar vortices. The underlying assumptions for the application of this technique were extensively discussed in recent years. However, the impact intrusions of mesospheric air into the polar stratosphere have on estimates of chemical ozone loss based on the ozone-tracer technique has not hitherto been studied. Here, we revisit observations of an intrusion of mesospheric air down to altitudes of similar to 25 km (similar to 600 K potential temperature) in the Arctic vortex in 2003. The mesospheric intrusion was identified in three balloon profiles in January and March 2003 as a strong enhancement in CO. In contrast, NOy was not enhanced in the mesospheric air relative to surrounding air masses as shown by the measurement in late March 2003. The measurements influenced by mesospheric air show ozone mixing ratios ranging between 3.6 and 5.6 ppm, which are clearly greater than those found in the "early vortex" reference relation employed to deduce chemical ozone loss. Thus the impact of intrusions of mesospheric air into the polar vortex on chemical ozone loss estimates based on ozone-tracer relations are likely small; the correlations cannot be affected in a way that would lead to an overestimate of ozone depletion. Therefore ozone-tracer relations may be used for deducing chemical ozone loss in Arctic winter 2002-2003. Here we use ILAS-II satellite measurements to deduce an average chemical ozone loss in the vortex core for the partial column 380-550 K of 37 +/- 11 Dobson units in March and of 50 +/- 10 Dobson units in April 2003.